Healthcare professionals’ experiences on interdisciplinary collaboration in a medical department of a Malaysian general hospital - Ang, Wei Chern; Abd Rahim SN; Abd Rahman NF; Muhamad Shukri N; Rokimi WR; Ng, SC (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Healthcare professionals (HCPs) in all healthcare facilities including public hospitals in Malaysia need to cooperate to meet the diverse healthcare demands. To date, there has yet detailed research on this collaboration in Malaysia. This study aimed to explore interdisciplinary collaboration in the Medical Department (wards and clinics) of a state hospital. Four focus group discussions (FGDs) were held. A medical specialist, medical officer, nurse manager/charge nurse, staff nurse, senior and junior clinical pharmacists were all present at each FGD. Purposive sampling was used to recruit participants (nomination by heads of department). FGDs were performed in English, but responses in Malay were accepted and translated into English. All FGDs were audio-recorded, transcribed, and analysed thematically. In the theme of role clarity, most participants opined that the doctors led in patient management, while the nurses were in charge of monitoring, ambulating and drug administration. However, some participants were unfamiliar with the role of pharmacists. The majority believed that effective collaboration did exist, but insufficient. Weak communication skills, lack of communication, personnel and time were obstacles to effective collaboration. Regular discussions between different disciplines can encourage interprofessional collaboration. Despite doctors acknowledging pharmacists' Medication Therapy Adherence Clinic (MTAC) services, and nurses' human immunodeficiency virus (HIV) counselling and diabetic education services, some nurses and pharmacists were unaware of each other's services. To avoid conflicting tasks and human resource wastage, each HCP's services should be actively promoted among other HCPs.